The Relationship of 4Ps Marketing Mix to the Satisfaction of Baturraden Local Tourists - Afifah, Hana; Hasibuan, Reza Rahmadi (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2022)
The aim of this study is to examine the relationship of 4P’s marketing mix which consists of Product, Price, Place, and Promotion as independent variables to the satisfaction of Baturraden local tourists as dependent variable. The quantitative method approach is implemented in this study which focused on Banyumas local tourists who have visited Lokawisata Baturraden. The sample size was calculated using Taro Yamane formula with the population based on the BPS data of Baturraden visitors in 2018, and the results obtained was 100 respondents. Five Likert Scale questioners were distributed to collect the data and Multiple Linier Regressions was employed for the analysis. The result showed that the variable Place has a significant effect to the Baturraden local tourists’ satisfaction with coefficient regression around 0.281 (28.1 percent), follows by Product with coefficient regression around 0.185 (18.5 percent). Meanwhile, other two variables such as price and promotion have no effects to the Baturraden local tourists’ satisfaction